The Effect of Health Education With Comic Media on The Level of Knowledge of Adolescent Girls About The Impact of Underage Marriage on Reproductive Health - Safitri, Diana (Tarqabin Nusantara Group, 2023)
Early marriage is often found in developing country such as in Indonesia. Mayority of Indonesian people is not understand the danger of pregnancy and children birth for mother in age less than 20 years old. Mother that not ready yet to pregnant can cause complication for mother and the baby, health education is very important to teenagers in order to early maariage rate is decrease. One of media that can use is comic. The purpose of this study is to analyze influence between health education with teenager knowledge about the impact of early marriage to reproduction health.A descriptive quantitative design utilized in this study. There were 67 respondent and 57 students were selected in this study taken by simple random sampling. A questionnaire is utilized in this study consisted of five parts: included the sosio-demographic data; the definition of early marriage; the definition of reproduction health, ideal age to marriage, and the impact of early marriage to reproduction health. Data was analyzed computerized by using SPSS 16. The result is there are a influence between health education with teenager knowledge about the impact of early marriage to reproduction health. By using Wilcoxon Match Pair the result is p= 0,000 with significancy 0,05. The conclusion from this study that comic media is effective to increase teenager knowledge about the impact of early marriage to reproduction health using comic media.